ANALISIS KEGIATAN EKTRAKULIKULER GERAKAN KEPANDUAN HIZBUL WATHAN TERHADAP PEMBENTUKAN JIWA LEADHERSHIP DAN KEMANDIRIAN SISWA DI MTs MUHAMMADIYAH 7 KANOR BOJONEGORO - arifin, zainal; Sholihah, Afidhatus (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2024)
Cultivating the Spirit of Leadership and Independence is an attitude that a leader needs to have in planning, thinking, learning responsibility for himself and others. A leader must be able to provide a good example for members and be able to direct each member to have traits that reflect leadership and should be formed from an early age in order to develop their potential. The purpose of this research is to find out the process of extra-curricular activities of the Hizbul Wathan Scout Movement towards the formation of a leader spirit, secondly to understand the process of extra-curricular activities of the Hizbul Wathan Scout movement towards the formation of a spirit of independence, third to find out the factors that influence the extra-curricular activities of the Hizbul Wathan Scout movement towards the formation of a spirit of leadership. and independence. This research uses a descriptive qualitative approach, data collection techniques using interviews, participant observation. This research uses a descriptive qualitative approach, data collection techniques using interviews, participant observation and documentation. Data analysis consists of organizing data, categorizing, looking for alternative data, writing reports and drawing conclusions. The results of the research concluded that first, using scouting materials and through educational training and intensive coaching, secondly carrying out training and Persami, these activities were held every 6 months. Third, the formation of the spirit of Leadership and independence of religious activities, Opening Ceremony, UN, Tali Menali, Sandi, Tadabur Alam. Through Hizbul Wathan's extra-curricular activities, students are little by little embedded in the spirit of leadership and independence. Penanaman Jiwa Leadhership dan Kemandirian merupakan sikap yang perlu dimiliki seorang pemimpin dalam melakukan rencana, berfikir, belajar tanggung jawab untuk dirinya maupun orang lain. Seorang pemimpin harus bisa memberikan teladan yang baik bagi anggota dan bisa mengarahkan setiap anggota untuk memiliki sifat yang mencerminkan kepemimpinan dan seharusnya dibentuk sejak dini Guna Mengembangkan Potensi yang dimliki. Tujuan dari Penelitian Ini  untuk mengetahui Proses Kegiatan Ektrakulikuler Gerakan Kepanduan Hizbul Wathan, terhadap Pembentukan Jiwa Leadhersip, Kedua untuk Megetauhi Proses Kegiatan Ektrakulikuler Gerakan Kepanduan Hizbul Wathan  terhadap Pembentukan Jiwa Kemandirian, Ketiga Mengetauhi Faktor yang mempengaruhi berlangsungnya  Kegiatan Ektrakulikuler Gerakan Kepanduan Hizbul Wathan  terhadap Pembentukan Jiwa Leadhersip dan kemandirian. Penelitian ini menggunakan pendekatan Kualitatif Deskriptif, tehnik pengumpulan data menggunakan wawancara, Observsi partisipan dan dokumentasi, Analisis data terdiri dari dari mengorganisasi data, mengkategorikan. mencari alternatif data menulis laporan dan menarik kesimpulan. Hasil dari Penelitian menyimpulkan Bahwa Pertama Menggunkan materi kepanduan dan melalui Pendidikan Latihan,serta pembinaan yang Intens, Kedua melaksanakan pelatihan-pelatihan dan Persami yang kegiatan tersebut dilaksankan 6 bulan sekali. Ketiga pembentukan jiwa Ledership dan kemandirian Melalui kegiatan keagamaan, Upacara Pembukaan, Pbb, Tali Menali, Sandi,Tadabur Alam, melalui kegiatan Ektrakulikuler Hizbul Wathan ini siswa sedikit demi sedikit Tertanam Pada diri siswa Jiwa Kepemimpinan Dan Kemandirian.